2018
DOI: 10.1504/ijwoe.2018.091336
|View full text |Cite
|
Sign up to set email alerts
|

Workplace flexibility and organisational citizenship behaviour: an investigation of the mediating role of engagement and moderating role of perceived fairness

Abstract: This study aims to better understand the effect of employee engagement and perceived fairness on positive workplace behaviour. Using the social exchange theory (SET) and agent-system model, this study investigated (a) the mediating role of employee engagement in linking workplace flexibility with organisational citizenship behaviour (OCB) and (b) the moderating role of perceived fairness in influencing the mediation. The conceptual model and defined hypotheses were measured using hierarchical multiple regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…It has many advantages over various other methods as it calculates reliability and validity at the same time (Ringle et al, 2012). In light of the studies conducted by Memon et al (2017) and Koon and Chong (2018), the current study focuses on prediction of endogenous variable and incremental character. The SMART-PLS (3.2.6) software was used to analyse data (Ringle et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…It has many advantages over various other methods as it calculates reliability and validity at the same time (Ringle et al, 2012). In light of the studies conducted by Memon et al (2017) and Koon and Chong (2018), the current study focuses on prediction of endogenous variable and incremental character. The SMART-PLS (3.2.6) software was used to analyse data (Ringle et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Four constructs (WLB implemented, perceived WLB, perceived performance appraisal and employee commitment) were measured where the fit among a series of confirmatory factor analysis models was compared to determining the best‐fit model. The fit of the models was measured using the procedures used by Koon and Chong (2018). The hypothesized four‐factor model exhibited the best fit (χ 2 (113) = 149.43, p < 0.01; CFI = 0.95; TLI = 0.94; RMSEA = 0.032).…”
Section: Resultsmentioning
confidence: 99%
“…Sekhar (2018) finds that providing flexible human resource management is directly related to engaging employees and performance. Koon (2018) says that implementing flexibility creates a positive behaviour attitude which increases performance and can engage the employees. Bal and Lange (2015) found that providing flexibility to the younger generation creates employee engagement and increases performance among the old age generation, so the outcome of providing flexibility will be subject to the age factor.…”
Section: Review Of Literaturementioning
confidence: 99%